Reimagining the Rural Hinterland: an investigation of participatory digital placemaking in rural communities - Rachael Ironside; Peter Reid (Culture Unbound: Journal of Current Cultural Research, 2024)
Rural locations often form a hinterland – geographically and culturally - for large conurbations that dominate a particular region. They are interconnected, sometimes interdependent, but also separated by the social and spatial perceptions of a place. For urban dwellers the hinterland is a place to ‘escape to the country’; for rural dwellers the town is the place of ‘bright lights’. The norms of either location often sit juxtaposed. This sense of place may be constructed from traditional, stereotypical ways of seeing and understanding communities. Digital technology has provided a platform to challenge these norms and provide new ways of representing the physical and cultural landscape of urban and rural spaces. In this conceptual paper we explore digital placemaking in the hinterland of the North-East of Scotland. In this region, the city (Aberdeen) dominates, but it is the rural hinterland that charms. Through an examination of co-created content of rural spaces in this region we consider the role of participatory digital placemaking. Drawing on an extensive body of previous research that has explored community heritage in the North-East of Scotland, we use case studies to consider the ways in which images, iconography and language shape and inform perceptions of the rural space in the digital environment. We argue that this bottom-up approach to placemaking in rural areas can help to shape the way that places are seen, understood, and valued by communities, visitors and wider online audiences. To conclude, this paper reflects on how rural participatory digital placemaking counteracts the urban norm and connects communities across town and country through a reimagined digital hinterland.